(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the impact of educational drama on the literary fifth grade students’ achievement in literature and texts.The researchers put the following zero hypothesis:"There is no statistically significant difference at the level (0.05) between the average achievement of female students of the experimental group who study literature and texts using educational drama, and the average achievement of female students of the control group who study the same subject in the traditional way." The researchers intentionally chose a school (Hind High School for Girls ) which includes two divisions for the fifth literary grade, and division (A) was chosen randomly to represent the control group